(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Based on the experimentation of different approaches and programmes, the term “rural development” refers to both a broader and more specific term. Often referred to as rural development, agriculture development is a broad spectrum that encompasses all avenues of development for rural areas, such as agriculture, industry and service industries. This comprehensive form takes into account not only development of agriculture sector activities, but also development of all activities in the rural sector including mines activity, urban and rural industries, social and economic infrastructure, community services, and rural human resources. As a discipline, rural development is arguably interdisciplinary in nature, requiring simultaneous transformation of such socio-economic, political, scientific, and cultural aspects of society bringing them together to diverge with a view to break any systemic and institutional constraints to development. As an important part of rural-development, the following are concerned with socio-economic processes, demographic and environmental factors, the restructuring of political and social structures, and the resultant improvement in productivity.